Using Citizen Science Within an Integrated Knowledge Translation (IKT) Approach to Explore Cardiovascular Disease Risk Perception in Rwanda - Niyibizi, Jean Berchmans; Nganabashaka, Jean Pierre; Ntawuyirushintege, Seleman; Tumusiime, David; Umwali, Ghislaine; Rulisa, Stephen; Nyandwi, Alypio; Okop, Kufre Joseph; Ntaganda, Evariste; Sell, Kerstin; Levitt, Naomi; Jessani, Nasreen S.; et al. (Frontiers in Tropical Diseases, 2021)
Background Collaborative approaches to generating knowledge between knowledge users (KUs) and researchers as a means of enhancing evidence-informed decision making have been gaining ground over the last few years. The principal study targeted rural and urban communities within the catchment areas of Cyanika health centre (Burera district, Northern Province) and Kacyiru health centre (Gasabo district, in City of Kigali), respectively to understand perceptions and preferences of communication with respect to cardiovascular disease (CVD) risk in Rwanda. This paper describes the integration of citizen science within an integrated knowledge translation (IKT) approach for this study. Methods The citizen science approach included deliberate, selective and targeted engagement of KUs at various steps throughout the study. It incorporated national and district levels stakeholders, primary health care stakeholders, local community leaders and influencers, and local community members (selected and trained to be termed citizen scientists) in the process of implementation. Data for this paper included minutes, reports and notes from meetings and workshops which were perused to report the immediate outcomes and challenges of citizen science within an IKT approach for a study such as described for Rwanda. Results As a result of a deliberate IKT strategy, key national stakeholders attended and contributed to all phases of citizen science implementation. Project-based and relationship-based immediate outcomes were documented. In line with local community health issues reported by the citizen scientists, the local community stakeholders pledged home grown solutions. These included enhancement of compliance to implement the “kitchen garden per household” policy, teaching local residents on preparation of healthy diet from locally available food items, organizing collective physical activity, fighting against locally made substandard beverages and teaching local residents on CVD (risk factors). As an indicator of the probable uptake of research evidence, district officials appreciated citizen scientists’ work and decided to consider presented results in their next fiscal year action plan. Conclusion Citizen science proved to be an important strategy for research co-production in Rwanda. While this strategy falls within the remit of a larger IKT approach it focuses on the role and ownership of research by local community residents. This study demonstrated that to improve the relevance and impact of research in local community a deliberate IKT approach that incorporates citizen science can be invaluable.